Youth patient and public involvement in health research in the Netherlands: experiences from a multi-stakeholder interview study - Femke Hilverda; Kaat Tielens; Violet Petit-Steeghs (Research Involvement and Engagement)
Abstract Background While patient and public involvement in health research is becoming gradually more common, there is still only limited involvement from children and adolescents. Especially in funded (health) research, youth has been found to be a hard to reach and vulnerable group. Previous literature argues that a responsive approach is needed. To obtain more insights into how such an approach can be perpetuated in funded health research projects, this study evaluated the experiences with youth involvement in health research from a multi-stakeholder perspective. Methods Youth involvement was evaluated in eight projects of six subsidy programs for health research. The RE-AIM model was used as an evaluation framework. This framework is useful to evaluate interventions on multiple levels (both on an individual and setting level), which makes it very applicable to a multi-stakeholder evaluation. For the evaluation, 24 in-depth interviews with seven program managers, six committee members, ten researchers, and six youth participants were performed. Results In the programs, approaches were used that are responsive to the context of the young participants such as a diverse, indirect and personal engagement approaches. Yet, difficulties in adapting to the needs of youth remain to exist due to the inflexible structure of the funded research process and limited time to explore diverse participation activities at multiple moments. As a result, the engagement of youth with a migration background or disability, were impeded. Conclusion To successfully implement youth patient and public involvement within funded health research, subsidy providers should allocate the necessary resources to create space for being responsive to the needs of young people.